Cavendish Banana (Musa acuminata) Plantlet Acclimatization in The Different Composition of Planting Media - nora augustien; sukendah sukendah; nova triani; noveni budi rahayuningsih (Gontor AGROTECH Science Journal, 2019)
Provide cavendish banana seedling massively can be solved with Provide cavendish banana seedling massively can be solved with tissue culture. One of the critical period in tissue culture is acclimatization. Acclimatization problem came from external factor, i.e. planting media. It causes cavendish banana plantlet got growth shambles and caused die. Planting media functions as growing media and nutrition source or fertilizer plant needed and hold the water within a certain time limit. Aside from, media necessity equilibration between micro and macro pore to keep stability between water, air and nutrition. Aimthis research was to understand the kind of the optimal media compositions in cavendish banana plantlet acclimatization. This research using Complete Randomized Design. Kind of compositions media used i.e. M1 = cocopeat : husk charhcoal : soil (1:1:2); M2 = cocopeat : husk charchcoal : compost (1:1:2); M3 = cocopeat : husk charchcoal : sand = (1:1:2). Observation variables were average of seedling growth precentage, plant height, addition of leaves, and growth of seedling phenotypes. Observation done on 15 daa (day after acclimatization) until 30 daa with interval 15 daa. The results showed that the all three treatments composition of planting media effected on seedling growth precentage, plant height andaddition of leaves. Observation in 30daa showed that planting media of cocopeat + husk charchcoal + sand having the best response treatment in parameter of seedling growth precentage, plant height andaddition of leaves.